A Family-Based Association Study of CYP11A1 and CYP11B1 Gene Polymorphisms With Autism in Chinese Trios. (May 2016) - Deng, Hong-Zhu; You, Cong; Xing, Yu; Chen, Kai-Yun; Zou, Xiao-Bing
Autism spectrum disorder is a group of neurodevelopmental disorders with the higher prevalence in males. Our previous studies have indicated lower progesterone levels in the children with autism spectrum disorder, suggesting involvement of the cytochrome P-450scc gene (CYP11A1) and cytochrome P-45011beta gene (CYP11B1) as candidate genes in autism spectrum disorder. The aim of this study was to investigate the family-based genetic association between single-nucleotide polymorphisms, rs2279357 in the CYP11A1 gene and rs4534 and rs4541 in the CYP11B1 gene and autism spectrum disorder in Chinese children, which were selected according to the location in the coding region and 5' and 3' regions and minor allele frequencies of greater than 0.05 in the Chinese populations. The transmission disequilibrium test and case-control association analyses were performed in 100 Chinese Han autism spectrum disorder family trios. The genotype and allele frequency of the 3 single-nucleotide polymorphisms had no statistical difference between the children with autism spectrum disorder and their parents ( P > .05). Transmission disequilibrium test analysis showed transmission disequilibrium of CYP11A1 gene rs2279357 single-nucleotide polymorphisms (χ 2 = 5.038, P < .001). Our findings provide further support for the hypothesis that a susceptibility gene for autism spectrum disorder exists within or near the CYP11A1 gene in the Han Chinese population.